2022
DOI: 10.3389/fbioe.2021.798393
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Vertical Alveolar Bone Augmentation Using Additive Manufacturing Technologies

Abstract: Vertical bone augmentation is aimed at regenerating bone extraskeletally (outside the skeletal envelope) in order to increase bone height. It is generally required in the case of moderate to severe atrophy of bone in the oral cavity due to tooth loss, trauma, or surgical resection. Currently utilized surgical techniques, such as autologous bone blocks, distraction osteogenesis, and Guided Bone Regeneration (GBR), have various limitations, including morbidity, compromised dimensional stability due to suboptimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Among biomaterials, bioceramics are one of the most commonly used materials in the field of bone regeneration because they have a similar composition to natural bone minerals, which have the characteristics of biocompatibility, biodegradation, bone inducibility and bone conductivity Frontiers in Bioengineering and Biotechnology frontiersin.org (Proussaefs, 2006;Lu et al, 2018;Wu et al, 2023). In many studies, bioceramics have been used as a space-maintaining devices to guide bone augmentation (Metz et al, 2020;Vaquette et al, 2021b). As an essential bioactive ceramic material, biphasic calcium phosphate ceramics are composed of hydroxyapatite (HA) and tricalcium phosphate (TCP) (Metz et al, 2020;Vaquette et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among biomaterials, bioceramics are one of the most commonly used materials in the field of bone regeneration because they have a similar composition to natural bone minerals, which have the characteristics of biocompatibility, biodegradation, bone inducibility and bone conductivity Frontiers in Bioengineering and Biotechnology frontiersin.org (Proussaefs, 2006;Lu et al, 2018;Wu et al, 2023). In many studies, bioceramics have been used as a space-maintaining devices to guide bone augmentation (Metz et al, 2020;Vaquette et al, 2021b). As an essential bioactive ceramic material, biphasic calcium phosphate ceramics are composed of hydroxyapatite (HA) and tricalcium phosphate (TCP) (Metz et al, 2020;Vaquette et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…The existing research has shown that the osteogenesis of vertical bone augmentation is often associated with an increase in pore diameter ( Franceschini Neto et al, 2019 ; Ghayor et al, 2021 ). More importantly, it has been observed that the optimal microarchitecture for bone augmentation differs from the optimal one for a general bone defect repair ( Jiang et al, 2018 ; Vaquette et al, 2021b ). This result suggests that the microstructure of the scaffold needs to be designed explicitly for vertical bone augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Too much loss of anatomical landmarks and too more the planned bone augmentation surface area in the design of the titanium mesh in the major bone defect/augmentation cases; as a result, the design of titanium mesh does not conform to the anatomical characteristics of the alveolar bone to wholly restore alveolar bone defects, making the area of bone augmentation excessive or insufficient [ 35 , 36 ]. On the contrary, there are more prominent anatomical landmarks and less surface area of planned bone augmentation in minor bone defect/augmentation cases, allowing the titanium mesh design to be as close as possible to the anatomical alveolar bone without gaps [ 37 , 38 ]. However, the results of this study do not support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, a major challenge to successful implant therapy is overcoming unfavorable host conditions including insufficient width and height of innate bone to receive an implant [32][33][34][35][36][37][38][39][40]. To achieve this, the execution and outcome of vertical bone augmentation require significant improvement [32,[41][42][43][44][45][46][47][48][49][50][51].…”
Section: Of 18mentioning
confidence: 99%